Destination Image, Hyperreality, Unreal Image Through Films. A Case Study of the Film Crazy Rich Asians - Sriganeshvarun, Nagaraj; Anil Aaron, Selvaram (INTI International University, 2020)
Crazy Rich Asians was one on the biggest hypes of cinema, from the Asian community and worldwide. It had an even bigger impact for Malaysians as Singapore was a stone throw away from Malaysia. The movie was a huge success within the Asian community, box office forking in international gross of $239 million, from just $30 million production budget. In October 2018, it was crowned the highest-grossing genre of romantic comedy from the last decade. However, the movie portrayal of Singapore was but a mere hyperreality and unreal image. Malaysia was a huge part of the film and was not given the credit it was due. The data was gathered using qualitative research method. In-depth interviews conducted with the sample, which were nine locals and 2 internationals selected based on criterion sampling. The data gathered was analysed based on 5 main themes, Tourism of Malaysia, portrayal of Malaysia, emotions of viewers, misrepresentation, and the awareness of viewers. Based on the data gathered locals and internationals viewers of the film feel negatively towards Crazy Rich Asians because of the potential that it could have on the Tourism of Malaysia. The respondent felt that the director could have given Malaysia its due credit rather than in the end credits.